Mordet i Finderup Lade og det tabte Pergamentcodex – eller Jagten på den Forsvundne Skat - Clausen, Svend (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2016)
Svend Clausen: The Murder in Finderup Barn and the vanished Parchment Codex, or Raiders of the Lost Manuscript In 1286 the Danish King Erik Klipping was murdered under mysterious circumstances in a barn in Finderup, Jutland. This murder has become one of the most iconic events in Danish history and its mysteries remain unsolved. The following year some apparent perpetrators were proscribed. Most of these were powerful Danish noblemen and the Royal official Lord High Constable Stig became the most notorious of these. The sentence has been heavily debated. Already during the 1500s and early 1600s these events were described by contemporary Danish historians. Their versions of events have generally not been deemed important as it was believed that they had their knowledge solely from sources still available today. This article, however, shows that historians of this age actually did possess a now lost parchment manuscript that most likely contained the source material from the original trial following the murder. The existence of this so-called Constable Stig-manuscript has been forgotten until now, but its existence can actually be verified with certainty from manuscript lists from this age – most clearly in a manuscript list from 1595. The manuscript is also mentioned in handwritten notes by Anders Sørensen Vedel, one of the renowned historians of that age. In footnotes he made references to this manuscript, because he used its textual contents for his historical works. Apparently the Constable Stig-manuscript is also mentioned in 1608, maybe then for the last time, and at some point after this it was lost and forgotten about. Likely it burned in 1728 together with the rest of the university library. Sadly, none of its most likely important textual contents survives today. Even a debate in the 1950s regarding the source material for this murder ultimately failed to bring this lost manuscript into renewed focus. Even though its source material remains sadly lost, the existence itself of this manuscript is still important: First of all, the existence of such a manuscript shows that an actual trial must have been held in the aftermath of the murder. Even this has seemed somewhat unclear, because of the scarcity of the preserved source material. Finally, the existence of this manuscript forces us to begin looking at the works of these old historians in a different way. In the coming years it will be important to examine the preserved historical works and manuscripts of these historians thoroughly to reveal whether this can shed any new light upon any of the lost source material from the Constable Stig-manuscript.